Viral diseases of fruit and berry crops in the South of the Russian Far East - Yu. G. Volkov; N. N. Kakareka; V. F. Tolkach; M. Yu. Shchelkanov (Юг России: экология, развитие, 2022)
Aim. To systematise data on pathogens of viral diseases of garden and berry crops in the south of the Russian Far East.Discussion. The peculiar climatic features of the Far East limit the range of garden and berry crops. However, there are a significant number of species of wild fruits and berry plants in the region, which have increased (often – record breaking) frost resistance and are therefore actively used for breeding new cultural forms. At the same time, for the last century and a half new varieties of garden crops have been actively introduced to the Far East, which has lead to an increase in the risk of penetration of entire phytovirus complexes together with vegetatively propagated (cuttings, vaccinations) plants. The greatest damage to garden crops in the Far East is caused by a number of representatives of the genus Nepovirus (Picornavirales: Secoviridae): Tomato ringspot virus, Arabis mosaic virus, Raspberry ringspot virus, Grapevine fanleaf virus, Grapevine linear pattern virus as well as several still unidentified viruses. Among other taxonomic groups of phytoviruses dangerous for fruit and berry crops one could point out Potato virus Y (Patatavirales: Potyviridae, Potyvirus), Carnation ringspot virus (Tolivirales: Tombusviridae, Dianthovirus), Clover yellow mosaic virus (Tymovirales: Alphaflexiviridae, Potexvirus), Cucumber mosaic virus (Martellivirales: Bromoviridae, Cucumovirus), Alfalfa mosaic virus (Martellivirales: Bromoviridae, Alfamovirus). The paper considers the species composition of aphids‐carriers of phytoviruses affecting garden crops of the region.Conclusions. In connection with the further prospects for the development of horticulture in the Russian Far East, it is necessary to intensify ecological and virological studies of this section of phytovirology as well as to increase access to agricultural producers with available test systems.